Analisis Pengaruh Kepercayaan, Brand Ambassador dan Review Online Terhadap Niat Pembelian Ulang Pada Situs Tokopedia di Kabupaten Klaten - Afifah Salsabila (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2024)
This research aims to determine the influence of trust, brand ambassadors and online reviews on repurchase intentions on the Tokopedia site in Klaten Regency. The population in this research is Tokopedia application users in Klaten Regency. The sampling technique in this research used non-probability sampling, with the type of sampling used being pursive sampling with a sample size of 96 respondents. The variables used in this research consist of two types of variables, namely independent (X) and dependent variables (Y). The independent variables in this research are trust, brand ambassadors, and online reviews. Meanwhile, the dependent variable used is repurchase intention. The data analysis method used is the multiple linear regression analysis method. Data processing uses the IBM SPSS Statistics application. The research results show that the variables of trust and online reviews have a positive and significant effect on repurchase intentions on the Tokopedia site in Klaten Regency. Meanwhile, the brand ambassador variable has no significant effect on repurchase intentions on the Tokopedia site in Klaten Regency.